La prueba ilícita penal en la administración de justicia en el Perú - Chávarry Correa, Ezequiel Baudelio (2011)
For the investigation work the national political reality has been poked. The facts that have constituted the source of this investigation have been the obtaining of tests without the due artificial formality, as the use of the vladivideos, petroaudios and the persecution to Montesinos. As antecedents they are considered the diverse forms of the penal illicit test in the administration of justice in the Peru located in the time and space, also the range of authors and their contributions valuable envelope the topic. The formulation of the problem is the following one: Which are the juridical-doctrinal dimensions for the admission and valuation of the penal illicit test in the jurisdictional decision in the Peru? The delimitation of the conceptual mark is divided in four chapters: Chapter I: The penal process and the principles of limitation of the probatory right. Chapter II: As for the chapter two The test and the relationship with the illicitness of the same one in the penal process. Chapter III: I study of the illicit test and theories on the illicit test, Theory of the exclusion Rule, the illicit test in the Peru. Chapter IV: Illegal evidence in Peru. The hypothesis is formulated in the following way: "The juridical-doctrinal dimensions for the admission and valuation of the penal illicit test in the jurisdictional decisions are: the conception of justice, the very juridical one guided, the defense of the fundamental rights of the actionable ones and the construction of a new society". The objective of the investigation is to base and to explain the doctrinal juridical dimensions for the admission and valuation of the penal illicit test in the administration of justice. The results and the discussion rotate around the following aspects: "The Justice in the XXI century", "The very juridical one guided in the elaboration of the illicit test", "The Fundamental Rights of the actionable ones and elaboration of the illicit test", "The administration of justice in the Peru: admission and valuation and "The illicit test in front of the construction of a new society. The most outstanding conclusion is that the imperious necessity exists of fomenting in the specialists of the Right, fundamentally in the operators and auxiliary of justice, the conviction of building a Penal Theory of the Human rights, outlawing the Illicit test, constituting it in an axis delimitante and normative sustenance of the administration of justice in the Peru.